Comparative Politics Globalizing World - HAYNES, Jeffrey (Polity, 2005)
This book offers an accessible and broadly conceived examination of the impact of globalization on comparative politics. Written in a lucid and lively style, it assumes no prior knowledge of either globalization or comparative politics, and is the ideal textbook for students who want to know more about these crucial topics.